Frontears, Theatre Performance, 2016, - Antoniou, Klitsa (My University, 2026)
Duration 16:52 16th Cyprus contemporary dance platform Cyprus at the Cyprus Contemporary Dance Festival Video art and Installation: Klitsa Antoniou Choreography: Elena Christodoulidou https://www.youtube.com/watch?v=GyHcJUqyJaI